Criminological Construction of Motives and Goals of Perpetrators of Criminal Acts of Detention from the Perspective of Modern Realism Theory - Ramli; Hajairin; Musmuliadin (Bulletin of Community Engagement, 2026)
This research stems from the academic problem of the limitations of the normative-dogmatic approach in criminal law, which tends to reduce the analysis of the crime of detention to merely fulfilling the elements of the crime, without elaborating on the perpetrator's motives and goals as complex social constructs. In fact, the dynamics of unlawful deprivation of liberty cannot be separated from power relations, opportunity structures, and individual rationality within a specific social context. This research aims to construct the motives and goals of perpetrators of the crime of detention through a synthesis of criminal law and modern realist criminological perspectives, specifically within the framework of Left Realism and Right Realism. The method used is library research with a normative-conceptual approach and theoretical analysis, through a systematic review of international criminal law and criminology literature. The results indicate that the perpetrator's motives reflect structural pressures and social dynamics, while the goals reflect a rational orientation in exploiting criminal opportunities. This theoretical synthesis produces a new construction model that expands the analysis of subjective elements in criminal law and provides academic and practical implications for the development of criminal policies that are more contextual, preventative, and responsive to the root causes of social problems.